WoundsWest: delivering comprehensive strategies to improve wound management in Western Australian Health Services - Prentice, Jenny; Strachan, V.; Carville, Keryln; Santamaria, Nick; Elmes, R.; Della, Phillip (Cambridge Media, 2009)
It is well known that prudent, supported, early discharge of patients back to their home environment facilitates recuperation, rehabilitation or palliation. Patients with wounds are no exception to this.The provision of effective ambulatory wound care is gaining increasing attention and importance worldwide as health services seek to provide efficient and effective services to growing numbers of patients with wounds, often under burgeoning fiscal constraints. The lack of, or poor utilisation of, evidence-based clinical practice guidelines and protocols for wound care and inequities in terms of access to resources, whether wound dressings or education, are causal factors leading to inconsistencies in the clinical management of wounds that contribute to less than optimal outcomes for patients with wounds.Health services and health managers' ability to strategically plan and rationalise wound management services is often further hindered by a lack of data on the epidemiology and potential burden of acute or chronic wounds within and on local or state health services. Furthermore, where there is an absence of clinical governance in relation to wounds, these wounds are not subject to the same scrutiny as other medical conditions and, therefore, opportunities to improve service delivery in relation to wound management are missed.This article describes a tripartite and multidimensional approach to providing West Australian public health services and employees with a sustainable system for the prediction, prevention and management of wounds. WoundsWest (WW), a partnership between WA Department of Health (WA Health), Silver Chain Nursing Association (Silver Chain) and Curtin University of Technology (Curtin University) is a novel, 6-year project and a first for Australia. WW aims to facilitate clinical governance of wounds within health services, enhance clinicians? knowledge, skill and competence in wound management, improve clinical outcomes for patients with wounds and increase health services' ability to decrease the burden of wounds in Western Australian public hospitals.In order to achieve these aims, WW established a number of subprojects to ascertain the prevalence of wounds within WA public hospitals, improve access to educational resources for wounds, improve access to expertise in wound management and provide a repository for wound-related data for the purpose of ongoing research.